Análisis y estrategias de diseño ecológico en quebradas urbanas Caso de estudio Quebrada El Rosal - Maurad Sánchez, Karen Jackeline (2018)
Abstract:The present work of end of titulation makes an analysis of the urban ravines of the city of Loja, specifically focusing on the ravine El Rosal, as a case study, being a sector that crosses problems of nature, economic, social, and environmental, whose origin is in the lack of care of those who live in their environment and the relevant authorities, which make it a forgotten and contaminated place despite the natural wealth that shows. The analysis is developed from a macro scale to a micro level, accompanied by an assessment using the use of study pixels, in order to obtain an effective diagnosis of the place, which guide us to the establishment of ecological design strategies, which are capable of to transform the level of degradation of the stream, without causing a negative environmental impact.